Экситоны в двумерном селениде вольфрама WSe 2 - Шварц, К.; Даулетбекова, А.; Сорокин , М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Excitons in two-dimensional tungsten selenide WSe2